Evaluation of the Soothing and Protective Properties of a Lignin Hydrolyzate - Letteria Greco; Salviana Ullo; Luigi Rigano; Marco Fontana; Enzo Berardesca (Cosmetics, 2019)
Lignins have shown remarkable antioxidant properties; acting as “scavengers” of free radicals physiologically produced by cell metabolisms; and exerting a protective action caused by the strong ability of these molecules to absorb UV radiation. Through preliminary Molecular Modeling studies and experimental studies in vivo and in vitro, a lignin hydrolysate compound has been shown to be an extremely versatile active ingredient, presenting soothing, anti-inflammatory, anti-itch, anti-oxidant, anti-aging and anti-pollution properties. The possible fields of application are therefore multiple; making this lignin hydrolysate a particularly interesting ingredient for topical dermatological compositions in the treatment of various skin disorders such as inflammation, edema, swelling, rash, redness, itching, chrono- and photo-induced skin aging. These manifestations are also the basis of more or less serious skin problems, making lignin hydrolysate capable of being used in cosmetic products for the eternal challenge of fighting skin aging, but also in medical devices that can be used to fight more painful and annoying symptoms, like those caused by dermatitis or psoriasis.